2022
DOI: 10.3389/fvets.2022.983110
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 expression in mammary invasive micropapillary carcinoma is associated with prognostic factors and acts as a potential therapeutic target in comparative oncology

Abstract: Pure human and canine mammary invasive micropapillary carcinoma is a rare malignant epithelial tumor accounting for 0.9 to 2% of all invasive mammary carcinomas and present a high rate of lymphatic invasion and metastasis, with unfavorable prognosis. Surgery and chemotherapy are standard treatments for almost all mammary cancer in both species, as well as hormonal and target therapies available for human patients. However, depending on the patient's clinical staging, satisfactory therapeutic results for invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Meanwhile, PTGS2 , also known as COX-2 , contributes to angiogenesis ( 42 ). COX-2 overexpression in colon cancer cells leads to the production of prostaglandins and the induction of pro-angiogenic factors such as vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), stimulating endothelial cell migration and tube formation ( 43 , 44 ). In our study, the high and low expression levels of TGFβ1 in different tumors exhibited significant differences, which also reflected the dual role of TGFβ1 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, PTGS2 , also known as COX-2 , contributes to angiogenesis ( 42 ). COX-2 overexpression in colon cancer cells leads to the production of prostaglandins and the induction of pro-angiogenic factors such as vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), stimulating endothelial cell migration and tube formation ( 43 , 44 ). In our study, the high and low expression levels of TGFβ1 in different tumors exhibited significant differences, which also reflected the dual role of TGFβ1 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, PTGS2, also known as COX-2, contributes to angiogenesis [42]. COX-2 overexpression in colon cancer cells leads to the production of prostaglandins and the induction of pro-angiogenic factors such as vascular endothelial growth factor (VEGF) and basic broblast growth factor (bFGF), stimulating endothelial cell migration and tube formation [43,44]. In our study, the high and low expression levels of TGFβ1 in different tumors showed great differences, which also re ected the dual role of TGFβ1.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, COX-2 plays a crucial role in cancer development through various cellular mechanisms like proliferation, mutation, angiogenesis, immune regulation, and tumor invasion. [32] SDF Q26-1-positive lymphatic vessels are primarily concentrated at the tumor invasive edge that facilitates metastasis. In IMPC tumor cells, the membrane-bound C-X-C chemokine receptor type 4(CXCR4) and stromal cell-derived factor-1(SDF-1)on lymphatic endothelial cell interaction is a pivotal step in lymphatic metastasis.…”
Section: Muc1mentioning
confidence: 99%
“…Thus, COX-2 plays a crucial role in cancer development through various cellular mechanisms like proliferation, mutation, angiogenesis, immune regulation, and tumor invasion. [ 32 ]…”
Section: Introductionmentioning
confidence: 99%